Different Amounts of Nitrogen Fertilizer Applications Alter the Bacterial Diversity and Community Structure in the Rhizosphere Soil of Sugarcane - Gu, Yan; Wang, Jihua; Cai, Weijun; Li, Guoliang; Mei, Yu; Yang, Shaohai (Frontiers in Microbiology, 2021)
Sugarcane cropping systems receive elevated application of nitrogen (N) fertilizer for higher production, which may cause production costs and environmental pollution. Therefore, it is critical to elucidate the response of soil microbial to the N fertilizer inputs in sugarcane soil. A field experiment was carried out to investigate the effects of optimum (N100, 375kg N/ha) and excessive (N150, 563kg N/ha) amounts of N fertilizer on soil bacterial diversity and community structure in a sugarcane cropping system by Miseq high-throughput sequencing. 50007 operational taxonomic units (OTUs) were obtained by sequencing the 16S rRNA gene amplicons. We found that excessive application of N fertilizers conversely obtained a lower yield, significantly decreased the pH and increased the available N in soils, and resulted in a relatively lower bacterial species richness. The hierarchical cluster tree and PCoA based on OUT suggested that different amounts of N application indeed change the bacterial community structures. The most abundant phyla across all soil samples were Proteobacteria, Actinobacteria, Acidobacteria, and Planctomycetes, which ensemble mean accounted for 74.29%. Excessive N significantly increased the relative abundance of phyla Proteobacteria, Acidobacteria and Bacteroidetes and the genera Sphingomonas, Gemmatimonas while optimum N treatment significantly increased the phyla Actinobacteria and the genera Bacillus, Nitrospira (P < 0.05). N application shifted the N cycle in nitrification, mainly on the Nitrospira but showed no significant effect on the genera related in nitrogen fixation, methane oxidation, sulfate reduction, and sulfur oxidation (P < 0.05). Overall, the optimum amount of N application might be condusive to beneficial microorganisms such as Actinobacteria, Nitrospira, and Bacillus and thus result in a more healthy ecosystem and higher sustainable crop production.